19th-Century Blambangan Society: The Dynamics of Religion and Culture in the Perspective of Islamic Historiography - Rahman, Abdur; Bis Sunan, M As Sabiq; Putri, Viona Aurillia (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The culture of Blambangan in the 19th century was shaped by interactions between Islam, local Hindu traditions, and the identity of the local community. As the last kingdom in East Java to uphold Hinduism following the fall of Majapahit, Blambangan—now more widely known as Banyuwangi—underwent sociocultural transformation due to the rise of Islam, which adapted harmoniously to local traditions. Islam entered the region through trade and preaching methods that accommodated indigenous customs. The 19th century marked a period of peace after conflicts between Blambangan and the Dutch East India Company (VOC). Although the armed struggles with the VOC and the Mataram Kingdom had ended, the Blambangan people developed the Osing culture as both a form of resistance and a cultural identity that preserved Hindu roots while integrating Islamic elements. This cultural blend of Islam and Hinduism gave rise to a developing society and a new social structure, which was formally recognized by the colonial government. In addition, the socio-political dynamics of the previous century—such as Wong Agung Wilis’s resistance against the VOC—also played a role in shaping the identity and consciousness of the Blambangan people. This study highlights the dynamic interaction between Islam and local culture, resulting in a unique and harmonious local identity in the 19th century amid broader social and political changes. This historical approach offers a deeper understanding of the process of religious and cultural acculturation, which contributed to the diversity and cultural richness of Blambangan.